2008
DOI: 10.1021/ja8036838
|View full text |Cite
|
Sign up to set email alerts
|

Doping Dependence of the Pressure Response of Tc in the SmO1-xFxFeAs Superconductors

Abstract: The superconducting transition temperature of the high-Tc SmO1-xFxFeAs superconductors increases monotonically as the F-doping level x increases to 0.20. High-pressure magnetization experiments reveal a strong sensitivity of Tc to interatomic distances in the underdoped regime (x Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
35
0

Year Published

2009
2009
2021
2021

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 45 publications
(40 citation statements)
references
References 11 publications
5
35
0
Order By: Relevance
“…Pressure dependence of T c has been widely investigated by the ρ(T ) and M(T ) measurements for R = Sm, 15,17,26,28,30 Nd, 14 Pr, 30 and Ce, 16,22,24 and negative pressure coefficients of T c have been found in these studies. In particular, the investigations in the high-pressure range have been done by the ρ(T ) measurements adopting the onset temperature of resistive drop as T c for R = Sm and Nd, resulting in dT c /dP ∼ −3.0 K/GPa.…”
Section: A Intrinsic T C -P Relationmentioning
confidence: 99%
See 2 more Smart Citations
“…Pressure dependence of T c has been widely investigated by the ρ(T ) and M(T ) measurements for R = Sm, 15,17,26,28,30 Nd, 14 Pr, 30 and Ce, 16,22,24 and negative pressure coefficients of T c have been found in these studies. In particular, the investigations in the high-pressure range have been done by the ρ(T ) measurements adopting the onset temperature of resistive drop as T c for R = Sm and Nd, resulting in dT c /dP ∼ −3.0 K/GPa.…”
Section: A Intrinsic T C -P Relationmentioning
confidence: 99%
“…The pressure effect for RFeAsO 1−x F x has been investigated by many researchers through the measurements of electrical resistivity (ρ), [12][13][14][15][16][17][18][19][20][22][23][24][25][26] ac and dc magnetization, [27][28][29][30][31] x-ray diffraction, 19,26,32 NMR, 23,33 and others. 20,31 For LaFeAsO 1−x F x with x = 0.11, it has been suggested that T c increases with increasing pressure P and shows a maximum of 43 K at P ∼ 4 GPa through the ρ(T ) measurements by determining T c from the onset of resistive drop.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…9 The shaded bars near x ~ 0.14 mark the boundary for different behaviour of the temperature-dependent resistivity. …”
Section: Synchrotron X-ray Diffractionmentioning
confidence: 99%
“…Under high pressure, T c of La-1111 increases from 28 K to 40 K, 16) while that of Sm-1111 decreases. 17) The effects of H doping seem to be not effective for optimum iron-based superconductors such as Sm-1111.…”
Section: Discussionmentioning
confidence: 99%